X-ray diffractive imaging of controlled gas-phase molecules: Toward imaging of dynamics in the molecular frame - Kierspel, Thomas; Morgan, Andrew; Wiese, Joss; Mullins, Terry; Aquila, Andy; Barty, Anton; Bean, Richard; Boll, Rebecca; Boutet, Sébastien; Bucksbaum, Philip; Chapman, Henry N.; Christensen, Lauge; et al. (My University, 2020)
We report experimental results on the diffractive imaging of three-dimensionally aligned 2,5-diiodothiophene molecules. The molecules were aligned by chirped near-infrared laser pulses, and their structure was probed at a photon energy of 9.5 keV (λ ≈ 130 pm) provided by the Linac Coherent Light Source. Diffracted photons were recorded on the Cornell–SLAC pixel array detector, and a two-dimensional diffraction pattern of the equilibrium structure of 2,5-diiodothiophene was recorded. The retrieved distance between the two iodine atoms agrees with the quantum-chemically calculated molecular structure to be within 5%. The experimental approach allows for the imaging of intrinsic molecular dynamics in the molecular frame, albeit this requires more experimental data, which should be readily available at upcoming high-repetition-rate facilities.